2021
DOI: 10.1038/s41598-021-97363-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel moisturized and antimicrobial hand gel based on zinc-aminoclay and Opuntia humifusa extract

Abstract: The high antimicrobial ability and low toxicity of zinc-aminoclay (ZnAC) are claimed in our previous reports. In this study, we formulate a novel hand gel based on ZnAC and Opuntia humifusa (O. humifusa) extract, which is a high moisturizing agent. The antimicrobial activity, cytotoxicity, moisturizing effect, and clinical skin irritation of the hand gel are evaluated. The hand gel with 0.5 wt.% ZnAC and 1.0 v/v% O. humifusa extract can kill more than 99% Escherichia coli (gram-negative bacteria) and Staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Nonetheless, those products often need to be supplemented with humectants, emollients, or moisturizers to avoid the effects of alcohol, which principally affect the epidermal layer, causing dehydration. Although dry skin does not represent a serious problem, it can lead to complications in the management of dermatological infections [ 132 , 133 ].…”
Section: Moisturizers Regenerative and Other Activitiesmentioning
confidence: 99%
“…Nonetheless, those products often need to be supplemented with humectants, emollients, or moisturizers to avoid the effects of alcohol, which principally affect the epidermal layer, causing dehydration. Although dry skin does not represent a serious problem, it can lead to complications in the management of dermatological infections [ 132 , 133 ].…”
Section: Moisturizers Regenerative and Other Activitiesmentioning
confidence: 99%
“…Opuntia humifusa extract (OHE) is high in total polyphenols and flavonoids, giving it antioxidant and antimicrobial activity, as well as high moisture retention capabilities [ 107 ]. OHE stimulates the expression of epidermal hyaluronic acid synthases (HAS) and regulates the synthesis of hyaluronic acid (HA), thereby reducing the expression of the hyaluronidase transcript and contributing to skin hydration [ 25 ]. Additionally, OHE has whitening and anti-wrinkle effects.…”
Section: Novel Antimicrobial Ingredients Of Hsgsmentioning
confidence: 99%
“…[7,12,63] The cytochalasins are fungal toxins with cell membrane permeability that exhibit structural diversity and several biological effects, such as cytotoxic, anticancer, antimicrobial and antiparasitic activities, inhibition of acetylcholinesterase enzyme in vitro and promotion of lysosomal function. [12,[64][65][66][67][68] 5-methylmelein is a known phytotoxic compound produced by Xylariaceae species, including Biscogniauxia mediterranea. [69,70] In other studies, caprylic acid and 5-methylmelein have shown antifungal, antibacterial, and cytotoxic activity.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…[10] Cactaceae also have a long history of use in the Americas for food, decoration and medicinal purposes. [11] In recent years, cacti have been explored in biotechnology as a source of bioactive compounds, used in the production of drugs [12] and as an alternative food. [13] In traditional communities, cacti are widely used for medicinal purposes such as treating diabetes, cholesterol, intestinal parasites, epilepsy, kidney function and improving digestion.…”
Section: Introductionmentioning
confidence: 99%